(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
This paper analyses the part played by some animals in the lusitanian and celtiberic religion from the literary assets over the hind of Sertorius and the epigraphic evidences of Cabeço das Fráguas, Lamas de Moledo and the altar of Marecos.